Potential Protective Role of Diabetes Mellitus on Aortic Aneurysms - Epstein, Eliza; Elefteriades, John A. (AORTA, 2025)
Prior research provided evidence that diabetes mellitus (DM) may convey protection to patients with abdominal aortic aneurysm (AAA) and/or thoracic aortic aneurysm (TAA).We sought recent publications that support or elaborate on this concept using PubMed and Cochrane, searching for publications that combine the search terms “aortic aneurysm” and “diabetes mellitus.” We collate and summarize evidence from the literature on this topic.We examined pertinent data on AAA, TAA, and aortic aneurysms in general (AA). Patients with DM have lower risk of developing AAA and a lower rate of growth of AAA. Patients with DM have a lower risk of mortality following hospitalizations for AA. That said, however, patients with DM who undergo AAA repair show higher risk of mortality. Patients with DM have lower aneurysm diameter and lower homocysteine and D-dimer levels. Research is emerging regarding a possible genetic explanation: the gene PSMD12 may play a role in the connection between AAA and DM. Patients with AAA taking diabetic medication metformin show reduced rate of growth of AAA as well as decreased mortality and complications. In TAA, however, no statistically significant differences in mortality or complications are consistently found. We find positive evidence to support the concept that diabetes does confer protection from AAA rupture. Current data does confirm significant protective effect for TAA.We confirm that metformin does exert protective properties. Diabetic protection against AAA may be mediated via Laplace's Law, as diabetic aortas have thicker walls, thus decreasing wall tension.
Keywords: abdominal aortic aneurysm; thoracic aortic aneurysm; diabetes mellitus